2012
DOI: 10.4028/www.scientific.net/kem.500.287
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Magnetorheological (MR) Jet Polishing of Mould Free Surface

Abstract: This paper attempts to use a kind of smart material-magnetorheological fluid and magnetorheological jet polishing method to polish mould. Use self-preparation MR fluid conduct experiments on MR jet polishing setup which developed by ourselves. After polished by MR jet, surface roughness of the mould improved from 812nm to 88nm. The result shows that experiment and its setup are feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It was also established that high precision surfaces can be manufactured by MJP with a roughness of <1 nm and in a range of materials, including glasses, single crystals, advanced ceramics, and metals. This technique offers a versatile solution for conformal optic imaging systems [97]. Numerous experimental studies have shown that the jet velocity, angle of impact, jet pressure, nozzle diameters, machining time, and magnetic field strength mainly affect the processing effect of MJP.…”
Section: Effect Of Processing Techniquementioning
confidence: 99%
“…It was also established that high precision surfaces can be manufactured by MJP with a roughness of <1 nm and in a range of materials, including glasses, single crystals, advanced ceramics, and metals. This technique offers a versatile solution for conformal optic imaging systems [97]. Numerous experimental studies have shown that the jet velocity, angle of impact, jet pressure, nozzle diameters, machining time, and magnetic field strength mainly affect the processing effect of MJP.…”
Section: Effect Of Processing Techniquementioning
confidence: 99%
“…The former entails physical and chemical reactions and mainly includes ion beam polishing [4,5] and laser polishing [6,7]. The latter entails mechanical action between the abrasive particles and the surface and mainly includes magnetorheological nishing (MRF) [9][10][11][12], ultrasonic-assisted polishing [14,15], bonnet polishing [17,18], and jet-assisted polishing [20][21][22]. Hänsel et al [4] were based on the dwell time algorithm and proved that, after global polishing of an aspheric silicon lens with an aperture of 135 mm by ion beam, the surface shape error was reduced from 4.5 to 0.56 nm.…”
Section: Introductionmentioning
confidence: 99%
“…By deploying the abrasive jet technology, Mandal et al [20] explored the in uence of various process parameters on the processing characteristics and obtained a maximum MRR of 1.08 g/min through optimization. Lu et al [21] used the magnetorheological jet polishing technology to spray the ceramic mold, and SR converged from 812nm to 88nm. Barletta et al [22] utilized the technology of uidized-bedassisted abrasive jet polishing Inconel 718 curved parts and studied the in uence of several factors, such as abrasive size and jet pressure, on its machining quality, which reduced SR to 0.1 µm, signi cantly improving the shape accuracy of the surface was improved.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these transformations are reversible and rapid. MRFs are widely used in machinery, construction, automobile and other fields because of these special properties [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%